1990
DOI: 10.1111/j.1464-5491.1990.tb01343.x
|View full text |Cite
|
Sign up to set email alerts
|

Rising Incidence of Type 1 Diabetes in Hungarian Children (1978–1987)

Abstract: A retrospective epidemiological study using primary data sources and external validation was conducted to assess the incidence of childhood (0 to 14 years) Type 1 diabetes in Hungary (excluding the Budapest region) over a 10-year period. Hospital records and regional diabetes centres' registries served as primary data sources, and data were validated by using the records of summer camps for diabetic children. The degree of ascertainment was 96.2%. Age-specific incidence rates increased until puberty with peak … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 13 publications
3
18
0
1
Order By: Relevance
“…The findings of this study are in agreement with other studies 4,7,9,[11][12][13][14]19 supporting the seasonality in T1DM diagnosis. Rosenbauer et al 22 found a greater number of children diagnosed with T1DM during the Summer-Autumn period as opposed to the Winter-Spring period.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The findings of this study are in agreement with other studies 4,7,9,[11][12][13][14]19 supporting the seasonality in T1DM diagnosis. Rosenbauer et al 22 found a greater number of children diagnosed with T1DM during the Summer-Autumn period as opposed to the Winter-Spring period.…”
Section: Discussionsupporting
confidence: 83%
“…3 Since then, there have been a number of studies demonstrating seasonality in the time of clinical presentation of T1DM, although a consistent and integrated picture on the actual seasonality of the disease has not been established. [4][5][6][7][8][9][10][11][12][13][14][15] It has been suggested that there is also a relationship between factors such as infections and vitamin D levels, and the seasonality of T1DM. [16][17][18] A recent meta-analysis of the data on seasonal variation in diabetes in 53 countries has suggested that seasonality in the diagnosis of T1DM is indeed a real phenomenon and that this seasonality pattern appears to be related to the geographical position, at least as far as the northern/ southern hemisphere is concerned.…”
Section: Introductionmentioning
confidence: 99%
“…Increases in the incidence of Type I diabetes have also been reported from other populations, e. g. from Sweden [10], Norway [11], Holland [12], Austria [13], Hungary [14], England [15,16]. Also outside of Europe a recent report from Kuwait indicated a major increase in incidence [17].…”
Section: Discussionmentioning
confidence: 86%
“…The involvement of androgens in the pathogenesis of the beta-cell specific autoimmune process has not been confirmed in man. However, it is known that the age-specific T1D incidence curve has its highest peak during puberty, and after pubertal years an increase in the male to female incidence ratio can be seen (20,21). These observations and the above mentioned experimental data suggest that androgen hormone action could be involved in be the pathogenesis of T1D.…”
Section: Introductionmentioning
confidence: 47%